2015
DOI: 10.1007/s00345-015-1644-y
|View full text |Cite
|
Sign up to set email alerts
|

Histologic subtype impacts cancer-specific survival in patients with sarcomatoid-variant renal cell carcinoma treated surgically

Abstract: Purpose To report survival outcomes of patients treated surgically for sarcomatoid-variant renal cell carcinomas (sRCC) and to assess whether the underlying histologic subtype is an independent predictor of outcome. Methods One hundred and fifty-one patients underwent surgery at a referral center between 1991 and 2014 and had sRCC in final pathology. Kaplan–Meier curves for metastasis-free survival and cancer-specific survival (CSS) were calculated, and the log-rank test assessed differences between clear ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
4
6
0
1
Order By: Relevance
“…Furthermore, we found histologic subtype to be a significant predictor of PFS and CSS, in keeping with previous studies [24,25]. However, studies of grade 4 RCC accounting for sarcomatoid differentiation and/or rhabdoid differentiation failed to show an independent association between histologic subtype and prognosis [18,20].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, we found histologic subtype to be a significant predictor of PFS and CSS, in keeping with previous studies [24,25]. However, studies of grade 4 RCC accounting for sarcomatoid differentiation and/or rhabdoid differentiation failed to show an independent association between histologic subtype and prognosis [18,20].…”
Section: Discussionsupporting
confidence: 91%
“…A majority of previous studies have attempted to risk stratify patients diagnosed with sRCC based on pathological features. 1 , 2 , 4 6 Similarly, a prior study that was reported by Kim et al 6 also found this results, in cM 0 setting, the tumors harboring much more %SD were more likely to suffer progression of disease and assert greater influence on OS. In their study, 50% as a cut-off point for %SD was not continue to analyzed when just found that 25% of SD can observed different influence on OS, in addition, Ki-67 index was not included in their study.…”
Section: Discussionsupporting
confidence: 66%
“…The histological features of SD can be observed in all types of RCC 25 ; ccRCC is the most common histological subtype, which accounts for about 65%–79% of all histological subtype with sarcomatoid dif ferentiation. 1 , 2 , 5 8 , 18 Nguyen et al 2 showed that histological subtype was associated with cancer-specific survival ( P =0.001) but not associated with distant metastasis ( P =0.8) in patients with sRCC and found that patients with ncRCCs were more likely to die from sRCC (HR: 2.3: 95% CI: 1.38–3.82) than ccRCC. In the targeted therapy period, Golshayan et al 17 found that patients with metastatic sRCC with underlying histological subtype of ccRCC were more likely to respond to VEGF-targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations